Enhanced electrochemical performance of CuCo2O4 nanowire arrays based solid-state symmetric supercapacitor by K3[Fe(CN)6] redox additive electrolyte. (July 2023) - Patil, Teja M.; Patil, Aravind H.; Krishnaiah, Mokurala; Mishra, Dhananjay; Kumar, Ajit; Kumar, Niraj; Chavan, Vijay D.; Kim, Deok-Kee; Patil, Sushant B.; Sadale, Shivaji B.; Patil, Raviraja T.; Fulari, Vijay J.; et al.
Abstract: The redox additive in an aqueous gel electrolyte is reported as one of the efficient methods to improve the electrochemical supercapacitor performance. Here, we report the role of redox additive, potassium ferricyanide((K3 [Fe(CN)6 ]), referred to as KFCN) for improving the electrochemical performance of binder-free, CuCo2 O4 (CCO) nanowire arrays (NWs) based solid state symmetric supercapacitors (SSCs). The crystal structure and morphology of prepared CCO films are confirmed by X-ray diffraction (XRD) and field emission-transmission electron microscopy (FE-TEM). The elemental composition of CCO films is estimated as Cu0.5 Co2.77 O3.82 via energy-dispersive X-ray spectroscopy (EDS) analysis. Surprisingly, the areal capacitance (or energy density at 5 mAcm −2 ) is significantly improved from 0.58 F cm −2 (or 0.016 mWh cm −2 ) to 10.5 F cm −2 (or 0.296 mWh cm −2 ), respectively, after the addition of KFCN to aqueous KOH electrolyte, as compared to bare KOH. Furthermore, CCO exhibits decent cyclic stability with 90 % capacitance retention up to 5000 CV cycles at the scan rate of 100 mV s −1 . Moreover, 2-terminal CCO NWs-based SSCs, employed with PVA-KOH-KFCN gel electrolyte, demonstrate a wider potential window of −0.9 to 0.9 V (1.8 V) with a 7-fold increase of energy density from 9.1 to 65 Wh kg −1, as compared with that of PVA-KOH gel electrolyte. As practical validation, the operation of Red-LED for 3 min is demonstrated with PVA-KOH-KFCN gel-based SSC, manifesting that adding redox substance in aqueous electrolytes is one of the promising strategies for portable and wearable energy storage systems. Graphical abstract: CuCo2 O4 NWs arrays based solid-state symmetric supercapacitor exhibit outstanding electrochemical performance in potassium ferricyanide [K3 Fe (CN)6 ] redox additive electrolyte. Unlabelled Image Highlights: Facile one-step synthesis of binder-free CuCo2 O4 NWs arrays. Electrochemical performance of CuCo2 O4 electrode in different concentrations of K3 Fe(CN)6 with 2 M KOH electrolytes. CuCo2 O4 /NF electrode exhibit aareal capacitance of 10.5 Fcm -2 in 2 M KOH + 0.050 M K3 Fe(CN)6 redox additive electrolyte. The energy density of a SSC fabricated in PVA-KOH-KFCN gel electrolyte is 65 Wh Kg −1 at a power density of 900 W Kg −1 .